Advantages and Losses Analysis on Burning Hours by The Production Planning Control in Determining Time Implementation of Maintenance Activities - Rahmawati, Fajar Khanif; Rakha, Humaid Iswahyu Hafizh (Institut Teknologi Dirgantara Adisutjipto, 2021)
Burning Hours is the one of policy in scheduling aircraft maintenance. With the burning hours the operator could performed aircraft maintenance before the due time. Burning Hours is indeed beneficial for flight operators to maintain the stability of the safety of the aircraft operation. Using the quantitative analysis method with the sample data’s from two aircraft, found that the burning hours affects to Burning Hours Cost loss for every aircraft meintenance activity. The value of Burning Hours Cost Loss and Potential Lost per Day needs to be considered by operators in scheduling maintenance activities, because it is possible that Burning Hours cannot be avoided in aircraft operation. Based on the data processing, the value of burning hours cost lost is not more than limit of potential lost per day. However it should also be considered if burning hours applied continuously will increase maintenance cost. Therefore, between maintenance planning department and the operation department should keep good coordination to minimize the burning hours cost loss. Keywords: Planning, Maintenance, Burning Hours